Mulheres em privação de liberdade e hiv/aids: um estudo de representações sociais - Pinho , Tatiana Ataíde Melo de (2016)
Introduction: In recent years, there has been an increasing and progressive increase in the number of women deprived of their freedom and their contamination by the HIV virus. In this sense, this study becomes relevant to the implementation of actions that reinforcing strategic actions specifically at these women. Objectives: systematize the scientific production developed on the subject of HIV / AIDS among people deprived of their liberty in the period of 2003 to 2012; Identify the structure of social representations on HIV / AIDS by women in deprivation of liberty; Analyze the social representations in different groups of age. Method: It was an exploratory study of qualitative approach, using the theoretical contribution of the social representations. The research locus was the Maria Júlia Maranhão Rehabilitation Center, in the city of João Pessoa-PB, from October to November 2014. It was attended by 32 women, selected for convenience, divided into age of groups of: 20-30 years old and 50-60 years old. The data were collected from a semi-structured interview and processed with the help of SPSS, IRaMuTeQ and EVOC softwares. The project was approved by the Committee of Ethics and Research with human beings of the Hospital Universitário Lauro Wanderley / UFPB, under the opinion of nº 660.127. Results: three articles were originated from this research presented in the results and discussion. In the first one it was observed that from the 33 articles selected, the highest production was between 2010 to 2012 (63.6%), predominance of the quantitative approach (75.7%) and the majority of the researchs realized in the United States (57.6%); In the second one, it was identified as probable central core of social representations about HIV / AIDS the elements of prevention, fear, death, disease and distress, and in poor neighborhoods contempt, pain, preservative, and bad transmission; And in the third one, which gave rise to five classes. First class, modes of transmission, women associate HIV / Aids: nail pliers, needle, tattoo, sex, blood, syringe, wound, kiss and saliva; Second class, psychosocial aspects, includes the descriptions in which women associate HIV / AIDS with prejudice, negative experience, fear of loneliness, isolation and difficulty in facing the disease in prison; Third class, knowledge about HIV / AIDS, presents contents such as: very serious illness and, despite not having cure, can be treated with the "cocktail"; Fourth class, socio-affective dimensions, whose contents are fear, loneliness, sadness, suffering, distress, nervousness, sorrow, indifference, difficult, pain; And fifth class, sexual practices / prevention, AIDS is associated with intimate visit, sex, soap, vagina, mouth, married, lack, condom, woman, man. Conclusion: Representational contents on HIV / AIDS were associated with much more negative aspects than positive, although women presented knowledge about the disease, forms of contagion and prevention, they were not vulnerable to infection. It is expected that such results may provide subsidies for directing political strategies in order to ensure full care for those women living in deprivation of liberty.